2016
DOI: 10.3390/f7050109
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Disturbance History on Ground-Layer Plant Community Composition in British Columbia

Abstract: Plant communities are sensitive to perturbations and may display alternative recovery pathways depending on disturbance history. In sub-boreal lodgepole pine forests of central interior British Columbia, Canada, fire and logging are two widespread landscape disturbances that overlap in many regions. We asked whether cumulative, short-interval disturbance from logging and fire resulted in different ground-layer plant communities than resulted from fire alone. Using field-collected data, we compared the taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…, Romme et al. , Ton and Krawchuk ). Many legacy effects are likely to be related to previous fire history (the invisible mosaic), meaning that wildfires do not necessarily erase the effects of a previously established fire mosaic on vegetation structure.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Romme et al. , Ton and Krawchuk ). Many legacy effects are likely to be related to previous fire history (the invisible mosaic), meaning that wildfires do not necessarily erase the effects of a previously established fire mosaic on vegetation structure.…”
Section: Introductionmentioning
confidence: 97%
“…However, even very severe wildfires are usually heterogeneous, with different areas burning at different severities (Turner and Romme 1994, Perry et al 2011, Berry et al 2015, Tingley et al 2016, meaning that while large wildfires can homogenize fire age, there may not be a coincident reduction in the variability of vegetation structures within a landscape. Moreover, even in areas that are severely burned by wildfires, legacy effects of previous vegetation on post-fire vegetation structure can be substantial (Franklin et al 2000, Fontaine et al 2009, Johnstone et al 2016, Romme et al 2016, Ton and Krawchuk 2016. Many legacy effects are likely to be related to previous fire history (the invisible mosaic), meaning that wildfires do not necessarily erase the effects of a previously established fire mosaic on vegetation structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although Coleman et al (2008) reported that logged sites exhibited comparable postfire plant assemblages and successional trajectories to unlogged sites, subtle species-specific and structural differences were observed. Altered recovery trajectories were also indicated by a reduction in postfire P. contorta seedling densities, attributed to clear-cut-mediated seed source reductions (Ton and Krawchuk 2016). Altered recovery trajectories were also indicated by a reduction in postfire P. contorta seedling densities, attributed to clear-cut-mediated seed source reductions (Ton and Krawchuk 2016).…”
Section: Intensive Forest Management and Firementioning
confidence: 99%
“…For instance, reduced postfire regeneration was attributed to seed source reduction by a preceding fire (Taboada et al 2018), bark beetle outbreak (Harvey et al 2013), and clearcut logging operation (Ton and Krawchuk 2016). For instance, reduced postfire regeneration was attributed to seed source reduction by a preceding fire (Taboada et al 2018), bark beetle outbreak (Harvey et al 2013), and clearcut logging operation (Ton and Krawchuk 2016).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation